2001
DOI: 10.1002/prot.1113
|View full text |Cite
|
Sign up to set email alerts
|

A conserved helix‐unfolding motif in the naturally unfolded proteins

Abstract: Among the naturally unfolded proteins there are many polypeptides that retain an extended conformation in the absence of any apparent signal. Using sequence alignment and secondary structure prediction tools, a conserved (LS/SL)(D/E)(D/E)(D/E)X(E/D) motif is uncovered in the vicinity of the N-terminus of their unfolded helices. A comparison of these data with published observations allows one to propose that the (LS/SL)(D/E)(D/E)(D/E)X(E/D) motif is a helix-unfolding signal. Furthermore, the strong similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…On the other hand, CD studies indicate that phosphorylation of p27 by CK2 has direct structural and functional effects. These results may be interpreted by postulating that p27 in solution behaves like a naturally unfolded protein type II, according to the classification proposed by Zetina [Zetina, 2001]. This author has also suggested the existence of a helix motif that promotes protein unfolding.…”
Section: Kip2mentioning
confidence: 72%
“…On the other hand, CD studies indicate that phosphorylation of p27 by CK2 has direct structural and functional effects. These results may be interpreted by postulating that p27 in solution behaves like a naturally unfolded protein type II, according to the classification proposed by Zetina [Zetina, 2001]. This author has also suggested the existence of a helix motif that promotes protein unfolding.…”
Section: Kip2mentioning
confidence: 72%
“…Calcium-dependent VLS formation is affected by changes in DxDxD motifs and the C-terminal ␣-helix. Two potential calcium-coordinating domains upstream of the C-terminal ␣-helix could be responsible for the observed calcium switch in NSP5-directed VLS formation (12,24,35,45,(49)(50)(51). Here, we examined whether mutations in the potential calcium binding motifs and ␣-helical domains alter VLS formation and the calcium switch.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are already more than 300 substrates known for CK2, regulation of the kinase has been indicated, but on the other hand, CK2 has been reported to be constitutively active and not regulated (29,33). An investigation by Zetina, who has analyzed sequence-dependent helix unfolding in proteins, suggested that phosphorylation of the conserved motif (LS/SL)(D/ E)(D/E)(D/E)X(D/E) could stabilize helix unfolding (47). The sequence context of phosphorylated serine residue 249 ( 248 LS DDDDQ 254 ) in NS2 conforms to this conserved sequence except for the last residue.…”
Section: Discussionmentioning
confidence: 99%